Degradation of Silicone Rubber Insulators under the Effects of Carbon Smoke, Salt and Cement Deposits - Amin, S.; Choudry, M. A.; Azam, S. (The Nucleus, 2015)
This research was aimed at finding the worst pollutant for silicone rubber insulators. In this study silicone rubber insulators were carbon smoked, salt deposited and cement deposited in real field and then aged for 5000 hours under International Electrotechnical Commission (IEC) 5000 hours multi stress aging conditions. The samples were analyzed at different intervals by qualitative (surface morphology, hydrophobicity classification) and quantitative (Leakage Current Measurement, Fourier Transform Infrared (FTIR) Spectroscopy, Non Soluble Salt Density (NSSD) Measurements) techniques in order to investigate any degradation/ recovery which may occur in them. Silicone rubber insulators have shown excellent resistance to carbon smoke. It means they have also excellent resistance to tracking. The expected life under the effect of carbon smoke or any other carbon based pollutant will be very high. The shortest life is expected when silicone rubber insulator is exposed to salt. The estimated life under salt stress is 18 years. The results indicate that cement and carbon pollution does not affect the performance of SiR insulators to significant extent. During this study all the insulator specimens preserved excellent properties and performance. This work is particularly helpful for those thinking to adopt the silicone insulators for construction of new lines in different polluted environments.